2013
DOI: 10.1001/jama.2013.7832
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin, Steroids, and Epinephrine and Neurologically Favorable Survival After In-Hospital Cardiac Arrest

Abstract: clinicaltrials.gov Identifier: NCT00729794.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
341
6
34

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(386 citation statements)
references
References 39 publications
5
341
6
34
Order By: Relevance
“…138,139 2015 Evidence Summary: OHCA In OHCA, steroids have been evaluated in 1 RCT 140 and 1 observational study. 141 In these studies, steroids were not bundled as they were in the IHCA but studied as a sole treatment.…”
Section: Evidence Summary: Ihcamentioning
confidence: 99%
See 1 more Smart Citation
“…138,139 2015 Evidence Summary: OHCA In OHCA, steroids have been evaluated in 1 RCT 140 and 1 observational study. 141 In these studies, steroids were not bundled as they were in the IHCA but studied as a sole treatment.…”
Section: Evidence Summary: Ihcamentioning
confidence: 99%
“…In IHCA, the combination of intra-arrest vasopressin, epinephrine, and methylprednisolone and post-arrest hydrocortisone as described by Mentzelopoulos et al 139 may be considered; however, further studies are needed before recommending the routine use of this therapeutic strategy (Class IIb, LOE C-LD).…”
Section: Recommendations-newmentioning
confidence: 99%
“…Analyses from three trials [12][13][14] showed RR of shock reversal of 1.42 (95% CI 0.39-5.24), of survival to hospital discharge of 1.96 (95% CI 0.68-5.64), and of good neurological recovery at hospital discharge of 1.45 (95% CI 0.41-5.13) in favor of corticosteroids. Another trial of 268 adults with in-hospital cardiac arrest found an OR of return to spontaneous circulation of 2.98 (95% CI 1.39-6.40) and of survival to hospital discharge with good neurological outcome of 3.28 (95% CI 1.17-9.20) in favor of methylprednisolone (given during resuscitation), and a OR of survival to hospital discharge with good neurological outcome of 3.74 (95% CI 1.20-11.62) in favor of hydrocortisone (given for post-resuscitation shock) [15]. See Appendix 2 in Supplementary material for evidence profile.…”
Section: Rationalementioning
confidence: 99%
“…For example, because of the favorable results of a recent study, 28 some providers may ask for methylprednisolone during resuscitation efforts. New medications bring additional challenges to reducing medication errors; not only must new medications be added to code carts throughout the entire institution but also all personnel must become familiar with the dosing and delivery systems of the new medications, which with methylprednisolone may include the Act-O-Vial system.…”
Section: Other Challengesmentioning
confidence: 99%